Definition of Derivative if the limit exists as one real number.

Slides:



Advertisements
Similar presentations
When you see… Find the zeros You think…. To find the zeros...
Advertisements

1 Example 3 (a) Find the range of f(x) = 1/x with domain [1,  ). Solution The function f is decreasing on the interval [1,  ) from its largest value.
1.3 Functions Domain and Range Function notation Piecewise functions
3.3 Differentiation Formulas
Average rate of change Find the rate of change if it takes 3 hours to drive 210 miles. What is your average speed or velocity?
When you see… Find the zeros You think…. To find the zeros...
1 Example 2 Sketch the graph of the function Solution Observe that g is an even function, and hence its graph is symmetric with respect to the y-axis.
The derivative as the slope of the tangent line
Warm Up: h(x) is a composite function of f(x) and g(x). Find f(x) and g(x)
LIMITS INVOLVING INFINITY Mrs. Erickson Limits Involving Infinity Definition: y = b is a horizontal asymptote if either lim f(x) = b or lim f(x) = b.
1.7 Combination of Functions
2.2 Basic Differentiation Rules and Rates of Change.
AP CALCULUS AB Chapter 2: Limits and Continuity Section 2.2: Limits Involving Infinity.
Example: Later, though, we will meet functions, such as y = x 2 sinx, for which the product rule is the only possible method.
3.3: Rules of Differentiation Objective: Students will be able to… Apply the Power Rule, Sum and Difference Rule, Quotient and Product Rule for differentiation.
AP CALCULUS AB PRACTICE EXAM. 1)Multiply by clever form of 1 3 and 1/3.
DERIVATIVES 3. If it were always necessary to compute derivatives directly from the definition, as we did in the Section 3.2, then  Such computations.
1 When you see… Find the zeros You think…. 2 To find the zeros...
. A 12 B 6 C 1 D 0 E A 12 B 6 C 1 D 0 E -1.
If k(x) =f (g(x)), then k’(x) = f ’ ( g(x) ) g’(x) k(x) = sin( x 2 ) k’(x) = cos ( x 2 ) 2x.
Use the factor theorem to determine if h(x) is a factor of f(x).
What is the symmetry? f(x)= x 3 –x.
UNIT 1 ASSESSMENT PROJECT Skylar Larson seconds 1.50 seconds1.00 seconds 0.50 seconds 3.50 seconds3.00 seconds2.50 seconds2.00 seconds.
2.4 The Chain Rule Remember the composition of two functions? The chain rule is used when you have the composition of two functions.
AB Calculus Midterm Review Problems.
Definition of Derivative.  Definition   f‘(x): “f prime of x”  y‘ : “y prime” (what is a weakness of this notation?)  dy/dx : “dy dx” or, “the derivative.
HIGHER ORDER DERIVATIVES Product & Quotient Rule.
Objectives: 1.Be able to find the derivative of functions by applying the Product Rule. Critical Vocabulary: Derivative, Tangent Daily Warm-Up: Find the.
Powerpoint Templates Page 1 Powerpoint Templates Review Calculus.
7.1: Antiderivatives Objectives: To find the antiderivative of a function using the rules of antidifferentiation To find the indefinite integral To apply.
Basic Differentiation Rules and Rates of Change Section 2.2.
Chapter 4: Polynomial and Rational Functions. Warm Up: List the possible rational roots of the equation. g(x) = 3x x 3 – 7x 2 – 64x – The.
1 When you see… Find the zeros You think…. 2 To find the zeros...
2.2 Differentiation Techniques: The Power and Sum-Difference Rules 1.5.
Chapter 4: Polynomial and Rational Functions. Determine the roots of the polynomial 4-4 The Rational Root Theorem x 2 + 2x – 8 = 0.
Powerpoint Jeopardy Definition of Derivatives Basic Derivatives Equation of Tangent Line Product & Quotient Rule Chain Rule
Exponential & Logarithmic functions. Exponential Functions y= a x ; 1 ≠ a > 0,that’s a is a positive fraction or a number greater than 1 Case(1): a >
Chapter 2 Review Calculus. Given f(x), find f ‘ (x) USE THE QUOTIENT RULE.
The Product and Quotient Rules for Differentiation.
Trigonometry Review Find sin(  /4) = cos(  /4) = tan(  /4) = Find sin(  /4) = cos(  /4) = tan(  /4) = csc(  /4) = sec(  /4) = cot(  /4) = csc(
Exponential & Logarithmic functions. Exponential Functions y= a x ; 1 ≠ a > 0,that’s a is a positive fraction or a number greater than 1 Case(1): a >
When you see… Find the zeros You think…. To find the zeros...
Graphing Inverse Variations. A relationship that can be written in the form y = k/x, where k is a nonzero constant and x ≠ 0, is an inverse variation.
Chapter 3 sections 3.3 and 3.4 What is differentiation and what are the methods of differentiation?
When you see… Find the zeros You think…. To find the zeros...
Parametric Equations.. Graph {(800 t, 6 – 16t 2 ) | } x = 800 t y = 6 – 16t 2 x = 800 t y = 6 – 16t 2 x/800 = t y = 6 – 16 [x/800] 2. y = 6 – x 2 /40000.
Acceleration. Definition Any change in velocity is acceleration What are the possible causes of acceleration? Speeding up Slowing down Changing direction.
LIMITS DERIVATIVES GRAPHS INTEGRALS VOLUME
Unit 2 Polynomial and Rational Functions
Mean Value Theorem.
When you see… Find the zeros You think….
3.1 Polynomial & Exponential Derivatives
Functions JEOPARDY.
Techniques of Differentiation
When you see… Find the zeros You think….
Derivatives of Parametric Equations
When you see… Find the zeros You think….
2.2 Limits Involving Infinity
Rational Functions, Transformations
Daily Warm-Up: Find the derivative of the following functions
10.2 Parametric Tangents & Areas
4. THE DERIVATIVE (NPD).
Section 3.3 Piece Functions.
32 – Applications of the Derivative No Calculator
27 – Graphing Rational Functions No Calculator
Derivatives Jeopardy Rates of Change Q $100 Q $100 Q $100 Q $100
Graphing Inverse Variations
Exponential Functions and Their Graphs
Exponential Functions and Their Graphs
What is the domain and range for the function f(x) =
Presentation transcript:

Definition of Derivative if the limit exists as one real number.

If g(t) = t n then g'(t) = n t (n-1) If g(t) = t 4 + 3t + 1, find g’(t) If f(t) = t n then f ' (t) = n t (n-1) A. 4t B. 4t + 3 C. 4t D. 4t

If g(t) = t n then g'(t) = n t (n-1) If g(t) = t 4 + 3t + 1, find g’(t) A. 4t B. 4t + 3 C. 4t D. 4t

If g’(t) = 4t 3 + 3, find g’’(t) A. 4t B. 12t C. 12t 2 D. 4t If f(t) = t n then f ' (t) = n t (n-1)

If g’(t) = 4t 3 + 3, find g’’(t) A. 4t B. 12t C. 12t 2 D. 4t If f(t) = t n then f ' (t) = n t (n-1)

If h(x) =, find h’(x) If h(x) = x n then h' (x) = n x (n-1) If h(x) = x n then h' (x) = n x (n-1) h(x) = 4x -2 h(x) = 4x -2

h(x) = =4x -2 h’(x)= A. -8x x -11 B. 8x x -11 C. -8x x -9 D. 8x x -9 If h(x) = x n then h' (x) = n x (n-1)

If h(x) =, find h’(x) A. -8x x -11 B. 8x x -11 C. -8x x -9 D. 8x x -9 If h(x) = x n then h' (x) = n x (n-1)

Dist trvl by X-2 racing car t seconds after braking.#59 x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. Find the velocity for any t. Find the velocity for any t. Find the velocity when brakes applied. Find the velocity when brakes applied. When did it stop? When did it stop?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. Find the velocity for any t. Find the velocity for any t. x’(t) = t x’(t) = t

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the velocity when brakes applied. Find the velocity when brakes applied. x’(0) = 120 ft/sec x’(0) = 120 ft/sec

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the velocity when t = 2. Find the velocity when t = 2. x’(2) = 120 – 30(2) = 60 ft/sec x’(2) = 120 – 30(2) = 60 ft/sec

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the velocity when t = 2. Find the velocity when t = 2. x’(2) = 120 – 30(2) = 60 ft/sec x’(2) = 120 – 30(2) = 60 ft/sec What does positive 60 mean? What does positive 60 mean?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the velocity when t = 2. Find the velocity when t = 2. x’(2) = 120 – 30(2) = 60 ft/sec x’(2) = 120 – 30(2) = 60 ft/sec What does positive 60 mean? What does positive 60 mean? Car is increasing its distance from home. Car is increasing its distance from home.

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop? When the velocity is zero. When the velocity is zero.

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop? x’(t) = t = 0 x’(t) = t = 0

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop? x’(t) = t = 0 x’(t) = t = = 30 t 120 = 30 t 4 = t 4 = t

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop? x’(t) = t = 0 x’(t) = t = = 30 t 120 = 30 t 4 = t 4 = t This changes the domain of x to This changes the domain of x to

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t When did it stop? When did it stop? x’(t) = t = 0 x’(t) = t = = 30 t 120 = 30 t 4 = t 4 = t This changes the domain of x to [0,4]. This changes the domain of x to [0,4].

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2 defined on [0,4]. x(t) = 120 t – 15 t 2 defined on [0,4]. x’(t) = t x’(t) = t How far did it travel after hitting the brakes? How far did it travel after hitting the brakes?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2 defined on [0,4]. x(t) = 120 t – 15 t 2 defined on [0,4]. x’(t) = t x’(t) = t How far did it travel after hitting the brakes? How far did it travel after hitting the brakes? x(4) = 480 – 15*16 = 240 feet x(4) = 480 – 15*16 = 240 feet

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the acceleration, x’’(t). Find the acceleration, x’’(t).

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Find the acceleration, x’’(t). Find the acceleration, x’’(t). x’’(t) = -30 x’’(t) = -30

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Acceleration, x’’(t) = -30. Acceleration, x’’(t) = -30. What does the negative sign mean? What does the negative sign mean?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t Acceleration, x’’(t) = -30. Acceleration, x’’(t) = -30. What does the negative sign mean? What does the negative sign mean? Your foot is on the brakes. Your foot is on the brakes.

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t What is the range on [0,4]? What is the range on [0,4]?

Dist trvl by X-2 racing car t seconds after braking. 59. x(t) = 120 t – 15 t 2. x(t) = 120 t – 15 t 2. x’(t) = t x’(t) = t What is the range on [0,4]? What is the range on [0,4]? [0, 240] [0, 240]

Definition of Derivative if the limit exists as one real number.

Theorem 1 The product rule [f(x) g(x)]’ = copy diff. copy diff. f(x) g’(x) + g(x) f ’(x)

The product rule If k(x) = f(x) g(x), then k’(x) = f(x) g’(x) + g(x) f ’(x) Suppose k(x) = (3x 2 -2x) (4x 4 +1) k’(x) = (3x 2 -2x) (16x 3 ) + (4x 4 +1)(6x-2)

Theorem 1 The product rule [f(x) g(x)]’ = f(x) g’(x) + g(x) f ’(x)

The product rule [f(x) g(x)]’=f(x)g’(x) + g(x)f ’(x) If y =(x 2 -3x+1)(1/x+3x) find dy/dx dy/dx = (x 2 -3x+1)(-x -2 +3) + (1/x+3x) (2x-3)

If f(x) = x n then f ' (x) = n x (n-1) Ifthen

The product rule [f(x) g(x)]’ = f(x) g’(x) + g(x) f ’(x) [ (3x-1)]’ = (3) +(3x-1)

If y = (x-1)(3x 2 +2) find dy/dx or y’ A. 6x B. (x-1) 6x + (3x 2 +2) C. (x-1) 6x + (3x 2 +2)x D. 3x 2 +2

If y = (x-1)(3x 2 +2) find dy/dx or y’ A. 6x B. (x-1) 6x + (3x 2 +2) C. (x-1) 6x + (3x 2 +2)x D. 3x 2 +2

If y = (x 2 -x)(-3x 2 +2) find dy/dx or y’ A. (2x-1) (-6x) B. (x 2 -x)(-3x+2) + (-3x 2 +2)(2x-1) C. (x 2 -x)(-6x) + (-3x 2 +2)(2x-1)

If y = (x 2 -x)(-3x 2 +2) find dy/dx or y’ A. (2x-1) (-6x) B. (x 2 -x)(-3x+2) + (-3x 2 +2)(2x-1) C. (x 2 -x)(-6x) + (-3x 2 +2)(2x-1)

If y = (x 2 -x)(x 3 -3x 2 +2) find dy/dx or y’ A. (x 2 -x) (3x 2 - 6x) + (x 3 - 3x 2 +2) (2x-1) B. (x 2 -x) (2x-1) + (x 3 - 3x 2 +2 ) (3x 2 - 6x) C. (2x-1) (3x 2 - 6x) D. (x 2 -x) (3x 2 - 6x) - (x 3 - 3x 2 +2) (2x-1)

If y = (x 2 -x)(x 3 -3x 2 +2) find dy/dx or y’ A. (x 2 -x) (3x 2 - 6x) + (x 3 - 3x 2 +2) (2x-1) B. (x 2 -x) (2x-1) + (x 3 - 3x 2 +2 ) (3x 2 - 6x) C. (2x-1) (3x 2 - 6x) D. (x 2 -x) (3x 2 - 6x) - (x 3 - 3x 2 +2) (2x-1)

Theorem 2 The quotient rule

Never cancel across the minus sign

The quotient rule

If f(x)= find f ’(x) A. [(3x-4)2 – (2x-1)3] /(3x-4) 2 B. (3x-4)2 – (2x -1)(3) C. [(2x-1)3 – (3x-4)2] /(3x-4) 2

If f(x)= find f ’(x) A. [(3x-4)2 – (2x-1)3] /(3x-4) 2 B. (3x-4)2 – (2x -1)(3) C. [(2x-1)3 – (3x-4)2] /(3x-4) 2

If f(x)= find f ’(1) A. -11 B. -5 C. C.

If f(x)= find f ’(1) A. -11 B. -5 C. C.

If f(x)= f ’(1) = -5 Write the equation of the line tangent to f when x = 1.

If f(x)= f ’(1) = -5 Write the equation of the line tangent to f when x = 1. f(1) =

If f(x)= f ’(1) = -5 Write the equation of the line tangent to f when x = 1. f(1) = 2/(-1) = -2

If f(x)= & f ’(1) = -5 Write the eq. of the tan. line A. y + 1 = -5(x-1) B. y – 1 = -5(x-1) C. y = -5(x-1) D. y = 5(x-1) - 1 when x = 1.

If f(x)= & f ’(1) = -5 Write the eq. of the tan. line A. y + 1 = -5(x-1) B. y – 1 = -5(x-1) C. y = -5(x-1) D. y = 5(x-1) - 1 when x = 1.

If f(x)= where is the horizontal asymptote? A. d. n. e. B. y = 0 C. y = 2/3 D. y = 1

If f(x)= where is the horizontal asymptote? A. d. n. e. B. y = 0 C. y = 2/3 D. y = 1

If f(x)= where is the vertical asymptote? A. d. n. e. B. x = 1 C. x = 4/3 D. x = 3/2

If f(x)= where is the vertical asymptote? A. d. n. e. B. x = 1 C. x = 4/3 D. x = 3/2

Proof of the product rule k(x) = f(x) g(x)

Proving the product rule

The product rule

k’(x) = f(x) g’(x) + g(x) f ’(x)